The knowledge profile of patients with hypertension - A. V. Stewart; C. J. Eales; S. de Charmoy (AOSIS, 2000)
A sample of 62 patients at a hypertension clinic at a tertiary care hospital was interviewed to establish which factors contributed to poor knowledge. Patients were interviewed to establish basic demographic data, their own risk factors, various psycho-social factors as well as their knowledge of the disease process and risk factor management. A step-wise logistic regression was done to establish which factors were predictive of the knowledge of patients with hypertension. It was found that a good quality of life (p=0.003); normal sex-life (p=0.00); home language of English or Afrikaans (p=0.002); educational status (p=0.00) and annual income (0.01) were predictive of patients' knowledge. Patients with a better quality of life had better knowledge than those with a poor quality of life (p=0.05).